Securing women’s resource rights through gender-transformative approaches - Garner, Elisabeth; Hossain, Tasaffy; Alam, Khushbu; Zaman, Mehenaz (CIFOR-ICRAF, 2023)
The Global Initiative for Gender-transformative Approaches promotes and strengthens women’s land rights through the integration of gender-transformative approaches in International Fund for Agricultural Development (IFAD) rural development interventions by sharing learning to improve policies, tools and practices across projects across six countries. Our approach systematizes the knowledge and lessons generated and uses the IFAD and CGIAR scientific and communications infrastructure to target decisionmakers and development practitioners with demanddriven tools, guidelines, frameworks and knowledge products. This presentation will provide insights from the Bangladesh case study. A gender analysis, consisting of a sociolegal analysis with qualitative and quantitative data, provided insight into opportunities for social transformation within the context of an ongoing project. The main conclusion of the gender analysis in Bangladesh was that while dual-titling alone was not enough to change social attitudes about women’s control and access to land, additional training nested in long-standing and intersectoral efforts in a geographic area fostered shifts in these attitudes. More broadly, by looking across the six countries, this initiative reinforces the importance of local and focused understanding of gender analysis to collaboratively design gender-transformative approaches. The Initiative is coordinated by IFAD and implemented in partnership with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF), the International Food Policy Research Institute (IFPRI) and the Alliance of Bioversity International and the International Center for Tropical agriculture (CIAT).